Asymptotic behavior of solutions to an evolution equation for bidirectional surface waves in a convecting fluid - Mahmoudi, H.; Esfahani , A.; Mahmoudi, H.; Esfahani , A. (Institute of Mathematics, NAS of Ukraine, 2020)
UDC 517.9 We consider the Cauchy problem for an evolution equation modeling bidirectional surface waves in a convecting fluid. We study the existence, uniqueness, and asymptotic properties of global solutions to the initial value problem associated withthis equation in $R^n$. We obtain some polynomial decay estimates of the energy.